2010
DOI: 10.1038/bmt.2009.374
|View full text |Cite
|
Sign up to set email alerts
|

HLA-matched sibling transplantation with BM and CD34+-purified PBSCs in adult patients with high-risk severe aplastic anemia to overcome graft rejection without an increase in GVHD

Abstract: The transplantation of a large number of stem cells can overcome graft rejection but with the increased risk of GVHD. In this study, we analyzed the outcome of 32 adult patients with acquired severe aplastic anemia (SAA) who were at a high risk for graft rejection, including multiple transfusions (median 147 units, range 20-680) and long disease duration (median 67 months, range 3-347), and who had received both BM and CD34 þ -purified PBSCs from an HLA-matched sibling donor to reduce graft rejection. T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
4
11
1
Order By: Relevance
“…The use of PBSC or purified CD 34 + PBSC has been shown previously to improve engraftment and reduce rejection in patients with SAA who have been multiply transfused . Despite the use of PBSC as the graft source, the incidence of grade II–IV acute GVHD was only 26.7%, which is very similar to data published both from the CIBMTR and from the EBMT . The incidence of acute GVHD can probably be further reduced with the addition of drugs such as alemtuzumab to the conditioning although there may be higher rates of graft failure .…”
Section: Discussionsupporting
confidence: 72%
“…The use of PBSC or purified CD 34 + PBSC has been shown previously to improve engraftment and reduce rejection in patients with SAA who have been multiply transfused . Despite the use of PBSC as the graft source, the incidence of grade II–IV acute GVHD was only 26.7%, which is very similar to data published both from the CIBMTR and from the EBMT . The incidence of acute GVHD can probably be further reduced with the addition of drugs such as alemtuzumab to the conditioning although there may be higher rates of graft failure .…”
Section: Discussionsupporting
confidence: 72%
“…The mean proportion of CD341 cells in the Clini-MACS Prodigy-and CliniMACS Plus-selected products was similar in our study and in that of Spohn and colleagues: 93.6% versus 93.9%, respectively, for the Clini-MACS Prodigy and 95.7% versus 95.9% for the CliniMACS Plus. 14 Cho and colleagues 15 found that the mean proportion of CD341 cells in the CliniMAC Plus-selected products was 95.8%, Dvorak and colleagues 16 found the median proportion of cells expressing CD341 antigen in CliniMAC Plus-selected products was 97% (range, 87%-99%), and for the Blood and Marrow Transplant Clinical Trials Network the median was 96.7% (range, 61.5%-99.8%). 17 In our study the mean recovery of CD341 cells from the mobilized PBSC concentrates by the CliniMACS Prodigy was 51.4 6 8.2% compared to 65.1 6 15.7% with the CliniMACS Plus.…”
Section: Discussionmentioning
confidence: 99%
“…PBSC graft was occasionally used for previously heavily-transfused patients. 21 For GVHD prophylaxis, cyclosporin A (5 mg/kg IV at day − 1, then 3 mg/kg IV from day 0) with dose adjustments targeting a trough level of 200-250 ng/mL plus short-course methotrexate (10 mg/m 2 IV at days 1, 3, 6 and 11) were administered. When patients could tolerate oral intake of medication, cyclosporin A was switched to the equivalent-dose oral form targeting a trough level of 150-200 ng/mL.…”
Section: Introductionmentioning
confidence: 99%